THE SEXISM IN JANE AUSTEN’S PRIDE AND PREJUDICE - Wira Buana Manalu and Sri Minda Murni (LINGUISTICA, 2017)
This study deals with The Sexism in Jane Austen’s Pride and Prejudice. This study was aimed as analyzing the types of sexist language that was consisted in the story of the novel Pride and Prejudice and to show the discrimination of sex in the novel Pride and Prejudice. This research used qualitative research. The data was taken from the sentences in the novel Pride and Prejudice. The research deals with the theory which was conducted by Janet Holmes (2001), where she said there were three types of sexist language. There were three types of sexist language found in the novel Pride and Prejudice, they were English Metaphors (10,60 %), Marked and Unmarked (89,02 %), and Generalization (0,38 %). It was find that the Marked and Unmarked (89,02 %) dominantly used in the novel Pride and Prejudice to shows that there are discrimination, especially found in women side as the discriminated sex in the novel Pride and Prejudice.